Analysis of the Internet Marketing Strategy of AIESEC - Lačevová, Aneta (2014)
The Master's thesis focuses on analysing the data about the customers of the student organisation AIESEC collected between 2012 and 2014. The results show the various customer segments defined by university, faculty and year of study from which AIESEC gets its applicants, the successfulness in finding an internship of students from these segments, proportions of different programmes (and sub-programmes) that students apply for, most desired countries as internship destinations, most effective communication channels and the average time periods between the process parts of application, raise, match and realization. Based on the results and insights from theory which discusses the use of Internet in communication with youth, the author suggests specific improvements for AIESEC to acquire more customers. These suggestions focus on increasing the return on investment of the organisation by increasing the quality of the applications, but equally focus on increasing the quantity of new customers acquired and increasing the efficiency of the AIESEC process.